A Bibliometric Analysis Concerning Local Ecological Knowledge on Elasmobranchs and Chimaeras - Custodio Nascimento, Marina; Santos, Sérgio Ricardo; Vianna, Marcelo (Ethnobiology and Conservation, 2023)
The absence of historical data on endangered species poses a conservation and socio-environmental problem. It is currently estimated that about one-third of all Chondrichthyes are under some level of threat, with knowledge gaps for many species. The aim of this research was to carry out a scientometric analysis on the scientific production concerning Local Ecological Knowledge (LEK) on Chondrichthyes. Searches on the subject were carried out at the SciELO, Scopus and Web of Science databases. The retrieved publications were assessed and sorted by a list of inclusion criteria, totaling 120 articles. The findings indicate that studies concerning LEK applied to Chondrichthyes assessments have recently gained relevance. The studies were published in a wide variety of journals and by researchers from different countries. Most research was aimed at marine ecosystems, and interviewees were usually professional fishers. From 179 studied Chondrichthyes, most are large sharks with conspicuous diagnostic characters, such as Galeocerdo cuvier, Isurus oxyrinchus and Sphyrna lewini, mainly in publications focused on fisheries. Studies addressing ethnoknowledge as a historical data collection source are undoubtedly paramount, and the need for further investments aiming at research in countries with scarce data addressing other actors, themes and scarcely studied taxa, is clear.